2020
DOI: 10.1002/hed.26514
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck surgery during the coronavirus‐19 pandemic: The University of California San Francisco experience

Abstract: Background: Guidelines regarding head and neck surgical care have evolved during the coronavirus-19 (COVID-19) pandemic. Data on operative management have been limited. Methods: We compared two cohorts of patients undergoing head and neck or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 22 publications
3
43
0
Order By: Relevance
“…The results of this study are in concordance with the data from most other centres 18 , 19 , which clearly show that the postoperative outcomes remain unchanged with no added risk or a minimal risk of SARS-CoV-2 infections in healthcare personnel. Iyer et al reported that there was a reduction in number of cases (overall operative caseload) to about 60% of the pre-COVID-19 times in order to maintain adequate safety and implement protective measures for COVID-19 transmission 20 .…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study are in concordance with the data from most other centres 18 , 19 , which clearly show that the postoperative outcomes remain unchanged with no added risk or a minimal risk of SARS-CoV-2 infections in healthcare personnel. Iyer et al reported that there was a reduction in number of cases (overall operative caseload) to about 60% of the pre-COVID-19 times in order to maintain adequate safety and implement protective measures for COVID-19 transmission 20 .…”
Section: Discussionsupporting
confidence: 90%
“…40 Performing a preoperative nasopharyngeal swab in all patients with HNC was done to reduce the possibility of perioperative complications and to keep hospitals safe for other patients and staff. [41][42][43] HNCs arise from mucosal membranes and the diagnosis and treatment often involve potential viral exposure, dysphagia or airway compromise, and nasogastric or tracheotomy tubes, all factors potentially exposing health care providers to aerosolized virus. 41,44 In this scenario, social distancing and personal hygiene are mandatory to avoid spread of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…1 Flowchart of study selection process to an operated case of PTC [20], one regarding potential surgical candidates who underwent active surveillance [21]. Nine English language studies had appropriate data for systematic review [22][23][24][25][26][27][28][29][30].…”
Section: Study Selectionmentioning
confidence: 99%
“…These studies were performed across several countries: three in China [23,27,28], three in Italy [25,29,30], one in USA [26], one in Jordan [22], while the remaining one enrolled a cohort of patients from 26 countries [24]. They were seven single-center observational cohort studies [22,23,[25][26][27][28][29] and two were multi-center studies [24,30], all with a retrospective study design except for two prospective studies [24,28]. Overall, the studies took place between January and August 2020 in countries with community SARS-CoV-2 prevalence varying from low to high.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation